Hayboxes to save fuel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Haybox cooking is an ancient, well-tried method. After a short boiling time on the stove or fire, the cooking pot is put into a haybox and covered well. The insulation prevents heat loss and the food continues to cook without the need for further...